Analysis of Feeding Behavior and Family Food Security as a Stunting Risk Factor in Semarang City - Najib, Najib; Giyarsih, Sri Rum; Listyaningsih, Umi; Nawawi, Nawawi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Stunting can be caused by many factors, including how a mother feeds her child. How much a family eats and how secure their food supply affects the number of short toddlers. This study examines feeding behavior, family food security, and stunting in Semarang. Quantitative observational analytic case-control study of 83,397 stunting-risk families. This study included 100 Semarang families at risk of stunting, with 50 cases (cases) and 50 controls (controls). This study used univariate and bivariate analysis. The results of the bivariate analysis showed that there was a relationship between feeding behavior and the incidence of stunting in Semarang City (p value = 0.002, OR = 4.030, 95% CI 1.712–9.488). Children who are cared for with inappropriate feeding behavior have a significantly greater risk of experiencing stunting compared to children who are cared for with appropriate feeding behavior. In addition, the relationship between family food security and the incidence of stunting in the city of Semarang was also confirmed to be statistically significant (p value = 0.000, OR = 6.833, 95% CI 2.732-17.093). Children who are cared for in food-insecure families are six times more at risk of experiencing stunting compared to children who are cared for in food-secure families. Based on the research data, it can be concluded that there is a relationship between feeding behavior and family food security and the incidence of stunting in the city of Semarang.